Social networks as a space for reflection and resilient action in the face of climate change - Jhonny Saulo Villafuerte Holguín (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2019)
Introduction: This work has as objective to value the results of a research action project for that there is articulated the transference of contents, forums, and processes of exploration of the environment with the social networks Facebook, YouTube and WhatsApp during the period 2017-2019. Method: The sample is composed of 340 students of a public university of Ecuador. There is applied the model of Sinatra, Kardash, Taasoobshirazi and Lombardi to dock environmental problematic. Techniques of qualitative investigation are applied to collect the opinions of the participants, which are analyzed from the socio-critic approach. Results: There were identified actions directed to the reduction of the consumption of electricity, paper and drinking water in the university. Discussion: It is concluded that the social networks introduce the environmental education by means of the generation of virtual spaces that improve significant learning, the collaborative work and strengthen the resilience attitudes before the climate change.